INVENTARISASI POTENSI BIJI BESI DAERAH GUNUNG BATU BESI DESA MASEWE KECAMATAN PAMONA TIMUR, KABUPATEN POSO, PROPINSI SULAWESI TENGAH - -, Geni Dipatunggoro (Fakultas Teknik Geologi Universitas Padjadjaran, 2009)
Inventory of potency of iron ore mineral resources in Batu Besi Mountain Region, at the village of Masewe, Subdistric of East Pamona, Regenct of Poso, Provine of Central Sulawesi was sponsored by Energy and Mineral Resources Office of Region of Poso and conducted by Team of Geologists from Faculty of Geological Engineering, University of Padjadjaran Bandung.Iron ore mineral resources occur ultrabasic rock of Pompangeo Formation which is older than Cretaseous. Sevaral sample exhibit Fe content larger than 50% which have domestic and international marketing prospect especially in China